Forensic science degrees and careers online (Forensic Science Online.org)
"Welcome to the largest - and one of the oldest - resources solely dedicated to Forensic Science degrees and careers online. We have researched thousands of pages on the web, including specific forensic science programs at schools, colleges, and universities across the United States. Additionally, we have researched and reviewed some of the top career choices in forensic science"